Cardiovascular disease-related mortality and factors associated with cardiovascular events in the TREAT Asia HIV Observational Database (TAHOD) - R. Bijker (2019)
© 2019 British HIV Association Objectives: With aging of the HIV-positive population, cardiovascular disease (CVD) increasingly contributes to morbidity and mortality. We investigated CVD-related and other causes of death (CODs) and factors associated with CVD in a multi-country Asian HIV-positive cohort. Methods: Patient data from 2003–2017 were obtained from the Therapeutics, Research, Education and AIDS Training in Asia (TREAT Asia) HIV Observational Database (TAHOD). We included patients on antiretroviral therapy (ART) with > 1 day of follow-up. Cumulative incidences were plotted for CVD-related, AIDS-related, non-AIDS-related, and unknown CODs, and any CVD (i.e. fatal and nonfatal). Competing risk regression was used to assess risk factors of any CVD. Results: Of 8069 patients with a median follow-up of 7.3 years [interquartile range (IQR) 4.4–10.7 years], 378 patients died [incidence rate (IR) 6.2 per 1000 person-years (PY)], and this total included 22 CVD-related deaths (IR 0.36 per 1000 PY). Factors significantly associated with any CVD event (IR 2.2 per 1000 PY) were older age [sub-hazard ratio (sHR) 2.21; 95% confidence interval (CI) 1.36–3.58 for age 41–50 years; sHR 5.52; 95% CI 3.43–8.91 for ≥ 51 years, compared with < 40 years], high blood pressure (sHR 1.62; 95% CI 1.04–2.52), high total cholesterol (sHR 1.89; 95% CI 1.27–2.82), high triglycerides (sHR 1.55; 95% CI 1.02–2.37) and high body mass index (BMI) (sHR 1.66; 95% CI 1.12–2.46). CVD crude IRs were lower in the later ART initiation period and in lower middle- and upper middle-income countries. Conclusions: The development of fatal and nonfatal CVD events in our cohort was associated with older age, and treatable risk factors such as high blood pressure, triglycerides, total cholesterol and BMI. Lower CVD event rates in middle-income countries may indicate under-diagnosis of CVD in Asian-Pacific resource-limited settings.